3i+-9-7i+21=6i+-16+-24

Simple and best practice solution for 3i+-9-7i+21=6i+-16+-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3i+-9-7i+21=6i+-16+-24 equation:


Simplifying
3i + -9 + -7i + 21 = 6i + -16 + -24

Reorder the terms:
-9 + 21 + 3i + -7i = 6i + -16 + -24

Combine like terms: -9 + 21 = 12
12 + 3i + -7i = 6i + -16 + -24

Combine like terms: 3i + -7i = -4i
12 + -4i = 6i + -16 + -24

Reorder the terms:
12 + -4i = -16 + -24 + 6i

Combine like terms: -16 + -24 = -40
12 + -4i = -40 + 6i

Solving
12 + -4i = -40 + 6i

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-6i' to each side of the equation.
12 + -4i + -6i = -40 + 6i + -6i

Combine like terms: -4i + -6i = -10i
12 + -10i = -40 + 6i + -6i

Combine like terms: 6i + -6i = 0
12 + -10i = -40 + 0
12 + -10i = -40

Add '-12' to each side of the equation.
12 + -12 + -10i = -40 + -12

Combine like terms: 12 + -12 = 0
0 + -10i = -40 + -12
-10i = -40 + -12

Combine like terms: -40 + -12 = -52
-10i = -52

Divide each side by '-10'.
i = 5.2

Simplifying
i = 5.2

See similar equations:

| -10x-2x+3x= | | 2x-5(-3x+7)=-1 | | -20=-3x+8x | | 7r-9=-86 | | 4c+7-3c+8= | | -19=1-7p+8 | | 7r-2+5r=6r+6-4r | | 0.25+0.10(x-3)=1.1 | | 6y+3=4y-13 | | -4(23)= | | x+x+100=110 | | 100=8+9a | | 3(-6x+7)=-1 | | 2x+7(3x-11)=130 | | 2(46)= | | J-4k+7+2j-3k= | | 0=1-2x+1 | | (3-2(13))= | | x^2+7x=588 | | -4(3-2(13))= | | 7x-4=-2+11-9x-5 | | 3(1i-3)-7(1i+3)=4(2i-3) | | -2n-2n=-16 | | 8-3x=2x+5 | | 7(1x+9)=91 | | x+20+x+10+y-40=180 | | (3(13)+7)= | | 3x-5x+7=9-x-4 | | -81s^3+375z^3= | | -(34)n+1=-11 | | 5-(3)=1+2(r+3) | | -3=m |

Equations solver categories